Suboptimal stimulation by weak agonist epitope variants does not drive dysfunction of HIV-1-specific cytotoxic T lymphocyte clones. (1st August 2019) - Grossman, Mark A.; Hofmann, Christian; Ng, Hwee L.; Yang, Otto O.
Abstract : Objective: To assess whether weakly recognized epitope variants induce anergy in HIV-1-specific CD8 + T lymphocyte (CTL) clones as a mechanism of dysfunction. Design: HIV-1-specific CTL clones were exposed to suboptimally recognized epitope variants, and screened for anergy and other T-cell dysfunction markers, and subsequent capability to kill target cells bearing index epitope. Methods: In addition to the optimally recognized index epitope, two suboptimally recognized epitope variants were selected based on titration curves for killing of peptide-labeled target cells by three HIV-1-specific CTL clones targeting the epitopes SLYNTVATL (Gag 77-85, A * 02-restricted), RPAEPVPLQL (Rev 66-75, B * 07-restricted), and KRWIIMGLNK (Gag 263-272, B * 27-restricted). Consequences of suboptimal stimulation were assessed by cytokine secretion, gene expression, and capacity to kill index epitope-labeled target cells upon rechallenge. Results: Suboptimal recognition of epitope variants reduced cytokine production by CTL similarly to reduction in killing of target cells. Gene expression profiles after suboptimal stimulation demonstrated no patterns consistent with T-cell dysfunction due to anergy, exhaustion, or apoptosis. Preexposure of CTL to epitope variants had no discernable impact on their subsequent capacity to kill index epitope-bearing target cells. Conclusion: Our data explore the hypothesis that poorly recognized epitope variants not only facilitate HIV-1 evasion of CTL recognition, but also induce CTL dysfunction through suboptimal signaling causing anergy. However, the results do not suggest that suboptimal signaling induces anergy (or exhaustion or apoptosis), indicating that the major role of CTL epitope variation is likely viral escape.